The Links between Human Resources Management and Corporate and Human Resources Strategy - Szőke, Brigitta; Tóth, Eszter Ilona; Vanó, Péter (Acta Carolus Robertus, 2022)
The macroeconomic environment has a significant impact on the economic performance of organisations, and therefore has a significant impact on the management of human resources and the need to manage them. The legal regulation of the labour market is carried out by the parliament, the government and local government bodies. All these legal regulators have a major impact on human resource management by setting the conditions of employment and dismissal, the rights of workers and employers. Employee organisations are involved in both the employer and the employee as the representative of the employee's interests. In this way they also have a direct influence on the management of the workforce in their organisations. Consequently, workers' organisations can also assert their rights in labour legislation, thus indirectly influencing labour management to a large extent. Our research is based on the identification of various documents, policies and written strategies. The aim of our analysis is to examine whether strategic human resource management is feasible without properly established processes and policies. Furthermore, we will study the benefits that the adoption of a written human resources strategy can bring to organisations.
Keywords: human resources management; organisational and operational rules; corporate strategy; human resources strategy